Forecasting Russian foreign trade comparative advantages in the context of a potential WTO accession - Ivan Savin; Peter Winker (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
This paper proposes a new approach of forecasting prospective comparative advantages based on relative prices differences between countries in the context of economic liberalization. An empirical analysis based on the example of Central and East European countries that have already passed the transition period from specialization mainly in natural resource- and labor-intensive goods to high-tech goods confirms a significant influence of our prospective advantages on comparative advantages dynamics. Using this method we identify a set of industries in Russia that seem to be most promising for formation of comparative advantages in the context of its economic liberalization and joining the WTO agreements. These industries include high and medium technological industries like machinery building, pharmaceutical products, railway transport, electronic and medical equipment.
Keywords: 330; comparative advantage; competitive advantage; economy in transition; Balassa index; Lafay index